Anne-Marie AUTISSIER, Javier GÓMEZ-MONTERO, Anxo ABUÍN, Victor A. FERRETI, Rubén Lois GONZÁLEZ y Rainer WEHRHAHN, eds., "Urban Dynamics: Conflicts, Representations, Appropriations and Policies". Berlín, Peter Lang, 2018, 356 pp. - Tamames Gala, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Review of Anne-Marie AUTISSIER, Javier GÓMEZ-MONTERO, Anxo ABUÍN, Victor A. FERRETI, Rubén Lois GONZÁLEZ y Rainer WEHRHAHN, eds., "Urban Dynamics: Conflicts, Representations, Appropriations and Policies". Berlín, Peter Lang, 2018, 356 pp.
Keywords: Urbanism; Cultural Studies; Anne-Marie Autissier; Javier Gómez-Montero; Anxo Abuín; Victor A. Ferreti; Rubén Lois González; Rainer Wehrhahn